Expecting equality or efficiency? A factorial survey on the justice perception of regional redistributive policies - Gniza, Jan; Abraham, Martin; Lehmann, Isabella; Lorek, Kerstin (Regional Studies, 2022)
Keywords: Chancengleichheit

Gerechtigkeit schlägt Effizienz: Prinzipien der regionalen Umverteilung - Abraham, Martin; Brenner, Thomas; Eberle, Jonathan; Gniza, Jan; Lehmann, Isabella; Wardenburg, Sven; Wrede, Matthias (Sozialer Fortschritt: unabhängige Zeitschrift für Sozialpolitik, 2020)
Obwohl zur Angleichung regionaler Unterschiede in den Wirtschafts- und Lebensverhältnissen von der Politik regelmäßig Fördermaßnahmen eingesetzt werden, legen empirische Befunde nahe, dass deren Wirkung aus verschiedenen Perspektiven heraus beurteilt werden muss. Unter Rückgriff auf unterschiedliche Datenquellen zeigen wir empirisch, dass sich die Legitimität regionaler Umverteilungsmaßnahmen weniger aus ihrer (ökonomischen) Effizienz als der auf Gerechtigkeitsnormen beruhenden Einstellung der Bevölkerung speist. Vor dem Hintergrund der Befragungsergebnisse können die Effizienzeinbußen einer auf die schwächeren Regionen ausgerichteten Ausgleichspolitik allerdings als in der Bevölkerung mehrheitlich akzeptierte Kosten gewünschter Bedarfsgerechtigkeit angesehen werde
Keywords: Regionale Umverteilung; Finanzausgleich; Gerechtigkeit; Effizienz

How Can Employers Signal Trustworthiness to Job Seekers? Determinants of Employer Reputation - Abraham, Martin; Gniza, Jan; Ostermann, Kerstin (Rationality in Social Science, 2021)

Public Acceptance of Regional Redistribution in Germany: A Survey Experiment on the Perceived Deservingness of Regions - Gniza, Jan; Wrede, Matthias (Journal of Social Policy, 2022)
Many policies target the economic and social consequences of regional inequality. This study experimentally investigates factors explaining the public degree of consent to financial transfers to disadvantaged regions. The main hypothesis of this study is that most people use the deservingness-heuristic not only to judge individuals but also to judge regions. We argue that people advocate interregional transfers based on perceived deservingness determined by recipient region’s need, lack of responsibility for the need, likelihood of reciprocity, and by a shared identity. To support this hypothesis, we conducted a factorial survey in Germany asking respondents to rate transfers to needy regions under different hypothetical conditions. We demonstrate, as predicted by the deservingness hypothesis, that consent to transfers to other regions is positively influenced by the extent of need and, in particular, past effort of the recipient region as well as by a shared identity. The results suggest that regional policies are particularly accepted when they target needs caused by factors beyond the control of recipient regions.<br
Keywords: Chancengleichheit